Upaya Meningkatkan Hasil Belajar Siswa Melalui Penerapan Metode Pembelajaran Jigsaw Berbantuan Modul pada Siswa SMA Negeri 2 Labuapi - Aspari Aspari (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2020)
This study aims to improve student learning outcomes by using the Jigsaw learning method assisted by the hydrocarbon material module. This research is a classroom action research which consists of two cycles. Each cycle consists of planning the action, implementing the action, observing and reflecting. The subjects of this study were students of class XI MIPA 1 SMA Negeri 2 Labuapi. The data sources came from teachers and students. Data obtained through interviews, observation, tests, and questionnaires. The data analysis technique used is descriptive qualitative and quantitative analysis. The results showed that the module-assisted Jigsaw learning method could improve: (1) student learning outcomes in cognitive aspects from 41.5% in cycle I to 72.3% in cycle II and in affective aspects from 68.92% in cycle I to 77.56% in cycle II. The conclusion of this research is that the use of the module-assisted Jigsaw learning method can improve student learning outcomes on the subject matter of hydrocarbons in class XI MIPA 1 SMA Negeri 2 Labuapi.